Temporal Dynam ics of the Neuregulin–ErbB Network in the Murine Prefrontal Cortex across the Lifespan - Paterson, Clare (Cereb Cortex, 2020)
Neuregulin–ErbB signaling is essential for numerous functions in the developing, adult, and aging brain, particularly in the prefrontal cortex (PFC). Mouse models with disrupted Nrg and/or ErbB genes are relevant to psychiatric, developmental, and age-related disorders, displaying a range of abnormalities stemming from cortical circuitry impairment. Many of these models display nonoverlapping phenotypes dependent upon the gene target and timing of perturbation, suggesting that cortical expression of the Nrg–ErbB network undergoes temporal regulation across the lifespan. Here, we report a comprehensive temporal expression mapping study of the Nrg–ErbB signaling network in the mouse PFC across postnatal development through aging. We find that Nrg and ErbB genes display distinct expression profiles; moreover, splice isoforms of these genes are differentially expressed across the murine lifespan. We additionally find a developmental switch in ErbB4 splice isoform expression potentially mediated through coregulation of the lncRNA Miat expression. Our results are the first to comprehensively and quantitatively map the expression patterns of the Nrg–ErbB network in the mouse PFC across the postnatal lifespan and may help disentangle the pathway’s involvement in normal cortical sequences of events across the lifespan, as well as shedding light on the pathophysiological mechanisms of abnormal Nrg–ErbB signaling in neurological disease.